2015
DOI: 10.1016/j.jcis.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Faster droplet production by delayed surfactant-addition in two-phase microfluidics to form thermo-sensitive microgels

Abstract: Microfluidic droplet templating produces monodisperse particles of well controllable sizes, but this is limited by the necessity to operate microfluidic devices at low flow rates in the dripping regime. Here, the per-channel rate of droplet production could be substantially increased by delayed surfactant addition as applied and verified for microfluidic production of N-isopropylacrylamide based microgels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Microfluidic devices with a flow focusing geometry as shown in Fig. 1 were built by soft lithography as an array of channels in a polydimethylsiloxane (PDMS) matrix bonded to a glass slide (for details, see [5]). The dimensions of PDMS-devices with two subsequent junctions were 40 x 40 µm 2 for the feeding channel, 40 x 40 µm 2 for the first collection channel after the first junction, and 80 x 40 µm 2 (width x height) after the second junction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microfluidic devices with a flow focusing geometry as shown in Fig. 1 were built by soft lithography as an array of channels in a polydimethylsiloxane (PDMS) matrix bonded to a glass slide (for details, see [5]). The dimensions of PDMS-devices with two subsequent junctions were 40 x 40 µm 2 for the feeding channel, 40 x 40 µm 2 for the first collection channel after the first junction, and 80 x 40 µm 2 (width x height) after the second junction.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously confirmed that the per-channel productivity of N-isopropylacrylamide (NIPAAm) droplets can be increased by delayed surfactant addition using a relatively expensive, low-viscosity fluorocarbon oil (HFE) as phase 2/3 [5]. It remains to be shown if this concept holds true also for other continuous phases such as paraffin oil that is better compatible with industrially concerns of production costs.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sarvothaman et al developed a strategy that involves using fluoroalkyl polyethylene glycol copolymers to reduce protein adhesion, which causes droplet movements to fail [17]. Seiffert et al proposed faster droplet production by delayed surfactant-addition to push droplet-based microfluidics to an industrially relevant scale [18]. Pirbodaghi et al developed an accurate approach that entails using bright-field microscopy with white light illumination and a standard high-speed camera for studying the fluid dynamics of rapid processes within microfluidic devices [19].…”
Section: Introductionmentioning
confidence: 99%